Egyptian student perceptions of visual warnings on cigarette packs - Touta, Hala (AUC Knowledge Fountain, 2016)
This Thesis examines how Egyptian students perceive the visual warnings on cigarette packs. First the study presents some significant global and regional statistics alongside a history of cigarette manufacturing, social associations, and advertising from the twentieth century. Three theories are reconciled, namely the theories of Normative Influence, Fear Appeal, and the Protection Motivation Theory to fully capture why the Egyptian young people continue to smoke despite the disturbing graphic images that are required by law to be placed on the front and back of cigarette packs. In engaging with these theories, the study explains how the human psyche develops a protective or adverse mechanism and how an individual's self-perception largely depends upon others' perception of him/her, precisely the perception of family and peers. Through focus group interviews, the study captures the complexity of smoking behavior while being conscientious of social, cultural and psychological factors affecting it. Finally the study proposes the themes that are found to be most effective in encouraging smoking cessation among young Egyptians.